Pulmonary rehabilitation in patients with idiopathic pulmonary fibrosis: Comparison with COPD - Arizono, Shinichi; Taniguchi, Hiroyuki; Sakamoto, Koji; Kondoh, Yasuhiro; Kimura, Tomoki; Kataoka, Kensuke; Ogawa, Tomoya; Watanabe, Fumiko; Tabira, Kazuyuki; Kozu, Ryo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: While the efficacy of pulmonary rehabilitation (PR) in chronic obstructive pulmonary disease (COPD) has been well established, emerging evidence also suggests its benefit in idiopathic pulmonary fibrosis (IPF). However, the differences and similarities between how PR affects diseases with different physiologies remain unknown. Objective: This study aimed to compare the efficacy of PR in COPD and IPF patients by performing multifactorial evaluation with various exercise capacity measurements, and dyspnea and health-related quality of life (QoL) assessment. Methods: Twenty-two IPF patients (%vital capacity: 72%) and 27 COPD patients (%forced expiratory volume1: 43%) were recruited. Subjects who completed a 10-week outpatient PR program were analyzed. We assessed five exercise capacity indicators (6-minute walking distance, incremental shuttle walking distance, endurance time, peak work rate, and peak values for oxygen uptake [peak VO2]), dyspnea (Baseline Dyspnea Index: BDI), and health-related QoL (St. George’s Respiratory Questionnaire: SGRQ) at baseline and immediately following completion of the PR program. Results: After 10 weeks of PR, all exercise capacity measurements, except VO2, as well as BDI and SGRQ score improved significantly (p